Finance and Development, September 1988. (Finance and Development; Finance and Development ;, 1988)
This paper describes the need to improve public finance for development. The paper underscores that public finance affects aggregate resource use and, together with monetary and exchange rate policies, influences the balance of payments, the accumulation of external debt, and the inflation, interest, and exchange rates. It highlights that public spending taxes, user charges, and borrowing also affect the behavior of producers and consumers, and influence the distribution of wealth and income in any economy.